Remote Sensing Detection of atmospheric pollutants using Lidar, Sodar and correlation with air quality data in an industrial area - Steffens, Juliana; Da Costa, Renata F.; Landulfo, Eduardo; Guardani, Roberto; F.moreira, Paulo; Held, Gerhard [UNESP] (SPIE, the international society for optics and photonics, 2011)
Optical remote sensing techniques have obvious advantages for monitoring gas and aerosol emissions, since they enable the operation over large distances, far from hostile environments, and fast processing of the measured signal. In this study two remote sensing devices, namely a Lidar (Light Detection and Ranging) for monitoring the vertical profile of backscattered light intensity, and a Sodar (Acoustic Radar, Sound Detection and Ranging) for monitoring the vertical profile of the wind vector were operated during specific periods. The acquired data were processed and compared with data of air quality obtained from ground level monitoring stations, in order to verify the possibility of using the remote sensing techniques to monitor industrial emissions. The campaigns were carried out in the area of the Environmental Research Center (Cepema) of the University of São Paulo, in the city of Cubatão, Brazil, a large industrial site, where numerous different industries are located, including an oil refinery, a steel plant, as well as fertilizer, cement and chemical/petrochemical plants. The local environmental problems caused by the industrial activities are aggravated by the climate and topography of the site, unfavorable to pollutant dispersion. Results of a campaign are presented for a 24- hour period, showing data of a Lidar, an air quality monitoring station and a Sodar. © 2011 SPIE.
Keywords: Air quality; Lidar technique; Sodar; Vertical profiles of lidar & sodar observations; Acoustic radars; Aerosol emissions; Air quality data; Air quality monitoring stations; Atmospheric pollutants; Backscattered light; Environmental problems; Environmental researches; Ground level; Hostile environments; Industrial activities; Industrial area; Industrial sites; LIDAR (light detection and ranging); Measured signals; Monitoring stations; Oil refineries; Optical remote sensing; Pollutant dispersions; Remote sensing techniques; Sensing devices; Sound detection and ranging; Steel plant; Vertical profile; Wind vectors; Cement industry; Gas emissions; Industrial emissions; Monitoring; Optical correlation; Petroleum refineries; Pollution detection; Remote sensing; Steelmaking; Tracking radar; Wind power; Optical radar